Aggravation of atrial arrhythmia by amiodarone during the perinatal period: A case report. Issue 7 (February 2019) - Ye, Fanhao; Jiang, Wenbing; Wang, Yi; Lin, Wei; Chen, Hao; Pan, Binglin
Abstract: Rationale: Amiodarone, a broad-spectrum antiarrhythmic drug, is widely used for the clinical treatment of tachyarrhythmias because of its safety and efficacy. Patient concerns: A 30-year-old woman presented with known paroxysmal atrial tachycardia and severe preeclampsia. Two days before admission, she had given birth to twins. She described her symptoms as a sudden palpitation at 10:20 accompanied by chest tightness and shortness of breath. Diagnosis: Cardiac arrhythmia and acute left heart failure. Interventions: Furosemide and sodium nitroprusside were administered to control the heart failure. At 16:20, 150 mg amiodarone (15 mg/min) was injected intravenously and continued at 1 mg/min. At 16:50, her electrocardiogram showed possible atrial tachycardia or atrial flutter with a ventricular rate of 206 beats/min. Administration of amiodarone was stopped at 17:23, and the medication was changed to esmolol. Outcomes: After 3 minutes, the palpitations stopped, the heart rate changed to a sinus rhythm, and the ventricular rate was 100 beats/min. Four days later, the patient underwent an electrophysiologic study and radiofrequency ablation. Lessons: When amiodarone is used to treat atrial arrhythmia, the ventricular rate may accelerate, which can cause patients with borderline heart failure to develop acute heart failure or further deterioration of acute heart failure. For heart failure induced or mediated by atrial arrhythmias, short-term β-blockers may be used to control the ventricular rate more quickly and effectively and to prevent the progression of heart failure.